Managing an Integrated Curriculum to Foster Students' Entrepreneurial Mindset: A Qualitative Study - Aziz Rofi'i; Ali Rohmat; Dahlia (Journal of Educational Management Research, 2026)
This study aims to examine and describe the management of an integrated curriculum combining the national and local curricula in fostering students’ entrepreneurial mindset, as well as to identify the supporting and inhibiting factors affecting its implementation. This study employed a qualitative field research design. Data were collected through observations, in-depth interviews, documentation, and questionnaires involving school leaders, teachers, administrators, and students. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, while data credibility was ensured through source triangulation. The findings reveal that the integrated curriculum management was implemented through the POAC management functions (Planning, Organizing, Actuating, and Controlling) by integrating the national curriculum, religious education, and local wisdom. The curriculum was delivered through contextual learning, project-based activities, entrepreneurship practices, and the utilization of local environmental resources. Students demonstrated positive responses toward entrepreneurship programs, particularly in creativity, practical experience, entrepreneurial interest, discipline, teamwork, and future orientation. The study implies that integrated curriculum management provides an effective strategy for developing students’ entrepreneurial character, life skills, and independence. Schools are encouraged to strengthen teacher capacity and diversify entrepreneurship programs to better accommodate students’ interests and talents.